JCV-specific T-cells producing IFN-gamma are differently associated with PmL occurrence in HIV patients and liver transplant recipients - Agrati, Chiara; Izzo, Luciano; Berno, Giulia; Cimini, Eleonora; Bordoni, Veronica; Giancola, Maria L; Baldini, Francesco; Colasanti, Marco; Ettorre, Giuseppe M; Izzo, Paolo; Pugliese, Federico; Angrisani, Marco; et al. (The New microbiologica, 2015)
Aim of this work was to investigate a possible correlation between the frequency of JCV-specific T-cells and PML occurrence in HIV-infected subjects and in liver transplant recipients. A significant decrease of JCV-specific T-cells was observed in HIV-PML subjects, highlighting a close relation between JCV-specific T-cell immune impairment and PML occurrence in HIV-subjects. Interestingly, liver-transplant recipients (LTR) showed a low frequency of JCV-specific T-cells, similar to HIV-PML subjects. Nevertheless, none of the enrolled LTR developed PML, suggesting the existence of different immunological mechanisms involved in the maintenance of a protective immune response in LTR.